Java EE 8 application development: develop enterprise applications using the latest versions of CDI, JAX-RS, JSON-B, JPA, Security, and more - Heffelfinger, David R (PACKT Publishing, 2017)
Develop Enterprise Java applications compliant with the latest version of the Java EE specification About This Book. This book covers all of the major Java EE 8 APIs and includes new additions such as enhanced Security, JSON-B Processing, and more. Learn additional Java EE APIs, such as the Java API for Websocket and the Java Message Service (JMS). Develop applications by taking advantage of the latest versions of CDI, Security, Servlets, and JSF and other Java EE specifications Who This Book Is For If you are a Java developer who wants to become proficient with Java EE 8, this book is ideal for you. You are expected to have some experience with Java and to have developed and deployed applications in the past, but you don't need any previous knowledge of Java EE. What You Will Learn. Develop and deploy Java EE applications. Embrace the latest additions to the Contexts and Dependency Injection (CDI) specification to develop Java EE applications. Develop web-based applications by utilizing the latest version of JavaServer Faces, JSF 2.3. Understand the steps needed to process JSON data with JSON-P and the new JSON-B Java EE API. Implement RESTful web services using the new JAX-RS 2.1 API, which also includes support for Server-Sent Events (SSE) and the new reactive client API In Detail Java EE is an Enterprise Java standard. Applications written to comply with the Java EE specification do not tie developers to a specific vendor; instead they can be deployed to any Java EE compliant application server. With this book, you'll get all the tools and techniques you need to build robust and scalable applications in Java EE 8. This book covers all the major Java EE 8 APIs including JSF 2.3, Enterprise JavaBeans (EJB) 3.2, Contexts and Dependency Injection (CDI) 2.0, the Java API for WebSockets, JAX-RS 2.1, Servlet 4.0, and more. The book begins by introducing you to Java EE 8 application development and goes on to cover all the major Java EE 8 APIs. It goes beyond the basics to develop Java EE applications that can be deployed to any Java EE 8 compliant application server. It also introduces advanced topics such as JSON-P and JSON-B, the Java APIs for JSON processing, and the Java API for JSON binding. These topics dive deep, explaining how the two APIs (the Model API and the Streaming API) are used to process JSON data. Moving on, we cover additional Java EE APIs, such as the Java API for Websocket and the Java Message Service (JMS), which allows loosely coupled, asynchronous communication. Further on, you'll discover ways to secure Java EE applications by taking advantage of the new Java EE Security API. Finally, you'll learn more about the RESTful web service development using the latest JAX-RS 2.1 specification. You'll also get to know techniques to develop cloud-ready microservices in Java EE. Style and approach The book takes a pragmatic approach, showing you various techniques to utilize new features of Java EE 8 specification. It is packed with clear, step-by-step instructions, practical examples, and straightforward explanations.